Acupressure for acute pain management in patients with hypertension: A two-case nursing study - Darmi Arda; Yongki Seran; Maria Kurni Menga; Suprapto Suprapto (Edukasi Ilmiah Indonesia, 2026)
Introduction: Hypertension is a major non-communicable disease frequently accompanied by acute pain, particularly headache and neck pain, which may reduce patient comfort and interfere with daily activities. Acupressure is a non-pharmacological nursing intervention that may support pain relief and promote relaxation in patients with hypertension. This study aimed to describe the application of acupressure management in reducing acute pain among hypertensive patients. Research Methodology: This study used a descriptive case study design involving two hypertensive patients with acute pain nursing problems. The intervention consisted of acupressure therapy applied to PC6 (Neiguan), LI11 (Quchi), LI4 (Hegu), GB20 (Fengchi), and LV3 (Taichong) acupoints for five consecutive days. Data were collected through interviews, observation, physical examination, blood pressure measurement, and pain intensity assessment using the Numerical Rating Scale. Data were analyzed descriptively by comparing clinical responses before and after the intervention. Because of the case study design and small sample size, odds ratio, beta coefficient, relative risk, 95% confidence interval, and p-value were not calculated. Results: Both patients showed gradual improvement after receiving acupressure therapy. In the first patient, pain intensity decreased from NRS 6 to 1, while in the second patient, pain intensity decreased from NRS 5 to 1. Blood pressure also showed a downward trend, accompanied by increased comfort and relaxation during the intervention period. Conclusion: Acupressure may serve as a feasible complementary nursing intervention for managing acute pain in hypertensive patients. Further studies with larger samples and controlled designs are needed to confirm its clinical effectiveness.